An ANFIS – Based Air Quality Model for Prediction of SO2 Concentration in Urban Area - Savic, Marija; Mihajlovic, Ivan; Zivkovic, Zivan (Serbian Journal of Management, 2013)
This paper presents the results of attempt to perform modeling of SO2 concentration in urban area in vicinity of copper smelter in Bor (Serbia), using ANFIS methodological approach. The aim of obtained model was to develop a prediction tool that will be used to calculate potential SO2 concentration, above prescribed limitation, based on input parameters. As predictors, both technogenic and meteorological input parameters were considered. Accordingly, the dependence of SO2 concentration was modeled as the function of wind speed, wind direction, air temperature, humidity and amount sulfur emitted from the pyrometallurgical process of sulfidic copper concentration treatment.